Regional Financial Interlinkages and Financial Contagion within Europe - Otker, Inci.; Arvai, Zsofia; Driessen, Karl. (Washington, D.C. : International Monetary Fund, 2009)
This paper focuses on financial interlinkages within Europe and potential contagion channeled through these interlinkages. It discusses the increased role of external financing as a source of funding for credit growth; analyzes potential channels of contagion through financial linkages; and assesses the magnitude of cross-border exposures between emerging and western European countries. Based on the stylized facts on these exposures, the paper provides simple indices of exposure to regional contagion that could help identify the likely pressure points and capture potential spillover effects and propagation channels of a regional shock originating from a given country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet